(untitled) (JONAH : Journal of Nursing and Homecare, 2025)
Hypertension is often found in the elderly, Hypertension is a condition without symptoms, where abnormally high pressure in the arteries causes an increased risk of stroke, heart failure, heart attack and kidney damage. The number of visits by elderly patients at UPTD Puskesmas Pekan Heran with cases of hypertension in 2024 will be 569 people. Non pharmacological therapies such as progressive muscle relaxation techniques have been proven to be effective in helping lower blood pressure. Objective: To describe blood pressure before and after applying progressive muscle relaxation techniques. Method: A case study was conducted on two elderly people who met the inclusion criteria, which was carried out on April 14-18 2025. The progressive muscle relaxation technique was given for five consecutive days, once a day for 15 minutes. Blood pressure was measured before and after the intervention. Results: Subject 1 experienced a decrease in blood pressure from 164/103 mmHg to 140/90 mmHg. Subject 2 experienced a decrease from 219/73 mmHg to 191/71 mmHg after applying the progressive muscle relaxation technique. Conclusion: The progressive muscle relaxation technique is effective in helping to lower blood pressure in elderly people with hypertension and can be used as a non pharmacological nursing intervention that is easy, safe, and without side effects.